2005
DOI: 10.1021/jf040199p
|View full text |Cite
|
Sign up to set email alerts
|

Azaphilones, Furanoisophthalides, and Amino Acids from the Extracts of Monascus pilosus-Fermented Rice (Red-Mold Rice) and Their Chemopreventive Effects

Abstract: Six azaphilones, monascin (1), ankaflavin (2), rubropunctatin (3), monascorburin (4), rubropunctamine (5), and monascorburamine (6), two furanoisophthalides, xanthomonasin A (7) and xanthomonasin B (8), and two amino acids, (+)-monascumic acid (9) and (-)-monascumic acid (10), isolated from the extracts of Monascus pilosus-fermented rice (red-mold rice) were evaluated for their inhibitory effects on 12-O-tetradecanoylphorbol-13-acetate (TPA)-induced inflammation in mice, on the induction of Epstein-Barr virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
149
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 16 publications
2
149
0
6
Order By: Relevance
“…All azaphilones showed weak to very weak antioxidant activities (Table 1) compared to the known standard, ascorbic acid. In particular, compounds (8)(9)(10) in group C were void of any activity, so the inhibition of NO production in RAW cells was not due to their free-radical scavenging activities.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…All azaphilones showed weak to very weak antioxidant activities (Table 1) compared to the known standard, ascorbic acid. In particular, compounds (8)(9)(10) in group C were void of any activity, so the inhibition of NO production in RAW cells was not due to their free-radical scavenging activities.…”
Section: Discussionmentioning
confidence: 96%
“…2,3) Although previous publications showed that azaphilones exhibit broad activities in many biological systems, such as cholesteryl ester transfer protein, 4) monoamine oxidase inhibition, 5) endothelin receptor binding, 6) the inhibition of gp120-CD4 binding, 7) telomerase inhibition, 8) the induction of Epstein-Barr virus, 9) and antimicrobial activities, 3,10,11) there is no report about the inhibition of nitric oxide (NO) production by azaphilones.…”
mentioning
confidence: 99%
“…RMR, a common fermented product of Monascus, has been used as a traditional cuisine and medicinal agent in Eastern Asia for several centuries. Currently, RMR is recognized as a functional food because of the proven benefits of some of its secondary metabolites, such as monacolins (cholesterollowering agents), 44 g-aminobutyric acid (hypotensive agent), 45 azaphilone pigments (anti-inflammatory agents) 46 and dimerumic acid, tannin, phenol and unsaturated fatty acids (antioxidants). 14,15 Monacolin K, also known as lovastatin, is usually the most abundant monacolin in RMR.…”
Section: Discussionmentioning
confidence: 99%
“…on health, including anti-osteoporotic (Cho et al, 2010), hypoglycemic (Lu et al, 2010), anti-tumor (Ho et al, 2010), neuro-protective , anti-atherosclerotic (Setnikar et al, 2005), anti-stress, anti-fatigue (Kim et al, 2002), and chemopreventive (Akihisa et al, 2005) activities, compared with non-fermented extracts. However, whether FRes have bifidogenic growth stimulating effects in vitro is not known.…”
Section: Fermented Rice Extracts (Fres) Have Various Beneficial Effectsmentioning
confidence: 99%